“Is there peace?”: Discrimination and the refugee experience in Malaysia - Nazri, Atika Shafinaz; Othman, Zarina; Talib@Khalid, Kart Aboo; Zainuddin, Emyzai (Masyarakat, Kebudayaan dan Politik, 2025)
Many factors, such as societal neglect, issues related to UNHCR, non-traditional legal frameworks, and international laws, contribute to the difficulties refugees face in Malaysia. However, in Malaysia, identify government discrimination as the primary factor contributing to the imbalance in refugees’ lives. Based on the experiences of refugees living in Malaysia, this research explores rights often denied by the government, regardless of their age, community background, or duration of stay. The study continues to delve into refugee challenges as long as they hold UNHCR cards. The method used in this study utilizes a qualitative approach. As a result of these challenges, this study presents the lived experiences of refugees as types of government discrimination based on their refugee status. This aspect has not been extensively explored in previous research. In conclusion, the study argues that those not involved in refugee management may perceive Malaysia as a country that practices democracy and upholds humanitarian values due to hosting nearly 180,000 refugees. However, the reality reveals existing shortcomings, including unrecognized UNHCR cards, fragility and susceptibility to detention, deprivation of the right to work, exposure to persecution, legal aid barriers, lack of access to healthcare treatment, and restricted access to formal education.